2014
DOI: 10.1039/c4ob00904e
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and photophysical characterisation of new fluorescent triazole adenine analogues

Abstract: Fluorescent nucleic acid base analogues are powerful probes of DNA structure. Here we describe the synthesis and photo-physical characterisation of a series of 2-(4-amino-5-(1H-1,2,3-triazol-4-yl)-7H-pyrrolo[2,3-d]pyrimidin-7-yl) and 2-(4-amino-3-(1H-1,2,3-triazol-4-yl)-1H-pyrazolo[3,4-d]pyrimidin-1-yl) analogues via Sonogashira cross-coupling and [3 + 2]-cycloaddition reactions as the key steps in the synthesis. Compounds with a nitrogen atom in position 8 showed an approximately ten-fold increase in quantum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 50 publications
(79 reference statements)
0
15
0
Order By: Relevance
“…1316 These studies have mainly concentrated on the application of 7-alkynyl derivatives of 7-deazapurines and 7-deazanucleosides for the preparation of the fluorescent 1,2,3-triazol-4-yl probes. 4,1718 Studies with 7-azido-7-deazapurine nucleosides as well as 8-azido- or 8-alkynyl-7-deazapurine nucleosides have received much less attention due to the lack of availability of the convenient synthetic protocols for their synthesis. 17,19 This is despite the fact that azidonucleosides 2022 including 8-azido as well as 8-alkynyl purine23 nucleosides have been used as convenient substrates for CuAAC and strain-promoted azide-alkyne cycloaddition (SPAAC).…”
mentioning
confidence: 99%
“…1316 These studies have mainly concentrated on the application of 7-alkynyl derivatives of 7-deazapurines and 7-deazanucleosides for the preparation of the fluorescent 1,2,3-triazol-4-yl probes. 4,1718 Studies with 7-azido-7-deazapurine nucleosides as well as 8-azido- or 8-alkynyl-7-deazapurine nucleosides have received much less attention due to the lack of availability of the convenient synthetic protocols for their synthesis. 17,19 This is despite the fact that azidonucleosides 2022 including 8-azido as well as 8-alkynyl purine23 nucleosides have been used as convenient substrates for CuAAC and strain-promoted azide-alkyne cycloaddition (SPAAC).…”
mentioning
confidence: 99%
“…When incorporated into nucleic acid, the FBAs have several advantages compared to the external and covalently attached fluorophores, for example, lower bulkiness, higher precision in orientation and position, and possibility of labelling close to the interested site. To date, a lot of FBAs have been developed and they have been successfully and extensively used in nucleic acid research . Early prototypical examples include the adenine analog 2AP, the cytosine analog pC, the pteridine analogs, the tricyclic cytosine analogs phenothiazine (tC) and phenoxazine (tC O ), and the triazole adenine analogs .…”
Section: Introductionmentioning
confidence: 99%
“…To date, a lot of FBAs have been developed and they have been successfully and extensively used in nucleic acid research. [7][8][9][10][11][12][13][14][15][16][17][18][19][20] Early prototypical examples include the adenine analog 2AP, [6,7] the cytosine analog pC, [8][9][10][11] the pteridine analogs, [12][13][14] the tricyclic cytosine analogs phenothiazine (tC) and phenoxazine (tC O ), [15][16][17][18] and the triazole adenine analogs. [19,20] Recent progresses include a tricyclic cytidine analogue with turn-on response to duplex formation, [21] a novel quadracyclic adenosine FRET pair, [22] a versatile and exceptionally bright fluorescent pentacyclic adenine analog, [23] an emissive interbase FRET pair, [24] and the emissive isomorphic RNA alphabets (th-bases and tz-bases).…”
mentioning
confidence: 99%
“…In general, the FBAs possess at least two characters: (a) they have high fluorescent activity so that they can be used as probes to study the interactions of nucleic acids with other biomolecules; (b) they are structurally and functionally similar to natural ones so as to cause only minimal perturbations to the delicately biochemical system. Nowadays, there are a wide variety of environment‐sensitive FBAs and they have been used extensively for biophysical and biochemical studies in nucleic acid research . For instance, the adenine analogue 2‐aminopurine is one of the most widely used fluorescent nucleobases, which can form Watson–Crick (WC) geometry with thymine or Wobble configuration with cytosine .…”
Section: Introductionmentioning
confidence: 99%
“…The cytosine analogue pyrrolocytosine and its derivatives have been used as site‐specific probes in numerous biochemical assays. Besides these examples, a lot of laboratories have reported the design and synthesis of various structurally unique FBAs to study nucleic acid dynamics . Hawkins's group has synthesized several fluorescent pteridine purine analogues, and it was found that their fluorescence is sensitive to microenvironment .…”
Section: Introductionmentioning
confidence: 99%